Numerical study on the impact load characteristics of a trans-media vehicle during high-speed water entry and flat turning. (1st April 2023) - Liu, Xiyan; Luo, Kai; Yuan, Xulong; Qi, Xiaobin
Abstract: When a trans-media vehicle enters water at high speed and turns while flat, the vehicle is subjected to vast impact loads. The impact on the structural strength of the vehicle cannot be ignored. In this paper, based on the fluid volume multiphase flow model and dynamic mesh technology, a coupling calculation method for the multiphase flow field and trajectory of a trans-media vehicle entering water at high speed is established. The accuracy and applicability of the numerical calculation method are verified by experiments. Through the numerical simulation, the typical water-entry and flat-turning process and the water-entry process with different water-entry velocities, water-entry angles and preset rudder angles are analyzed. The results show that the phenomenon of tail-slapping oscillation occurs in the process of high-speed water entry and flat turning. Under different water-entry conditions, the impact load characteristics of the vehicle are basically different, but the water-entry process is stable overall. Highlights: The coupling calculation method of a trans-media vehicle entering water at high speed is established. The high-speed water-entry experiment of the trans-media vehicle is carried out to verify the numerical method. The impact load characteristics of a trans-media vehicle during high-speed water entry and flat turning are investigated. The influences of different water entry parameters on the load characteristics are examined.